Composition and Potential Functions of Bacterial Communities Associated With Aurelia Polyps - Li, Yongxue; Hao, Wenjin; Peng, Saijun; Sun, Tingting; Zhao, Jianmin; Dong, Zhijun (Frontiers in Marine Science, 2022)
Jellyfish and their associated microbes form an ecological unit called the holobiont. Changes in the composition of dominant microbial assemblages may influence the environmental resilience and function of the holobionts. Differentiating the microbial communities from diverse jellyfish is essential for characterizing the functional contributions of microorganisms but has not been fully explored. In this study, based on 16S rRNA gene sequencing, we investigated the composition of microbial communities associated with two Aurelia polyp species (Aurelia coerulea and Aurelia solida) obtained from seven locations, which were maintained under the same environmental conditions. Sequence analysis showed that the genera Sphingomonas, Phyllobacterium, and Ralstonia were the most abundant members of the Aurelia-associated microbial communities and dominated the core microbiome of the Aurelia polyps in this study. Functional prediction revealed that chemoheterotrophy and aerobic chemoheterotrophy, based on the FAPROTAX dataset, were the primary functions of the associated microbes of Aurelia polyps. In addition, the comparison of microbial communities from different Aurelia polyp populations revealed interspecific instead of intraspecific variation, indicating a correlation between the composition of the symbiotic microbiota and genetic background of Aurelia polyps.